Are Humans the Most Intelligent Species? - Robert P. Erickson (Journal of Intelligence, 2014)
Hunt and Jaeggi [1] nicely summarize the point that within the academic field of intelligence, we do not have a commonly understandable definition of what intelligence is. Still the term is used extensively and with consensus to the effect that humans are the most intelligent species. An example is given of this problem, and a definition and solution are suggested.